Living related liver transplantation for hepatitis B–related liver disease without hepatitis B immune globulin prophylaxis. Issue 9 (18th August 2013) - Wadhawan, Manav; Gupta, Subash; Goyal, Neerav; Taneja, Sunil; Kumar, Ajay
<x xml:space="preserve">Abstract</x> Hepatitis B immune globulin (HBIG) is routinely used in liver transplantation for hepatitis B virus (HBV)–related liver disease. With potent oral antivirals, HBIG may not be required. We conducted a prospective trial to evaluate living related liver transplantation (LRLT) without HBIG. Eighty‐nine patients with HBV‐related liver disease underwent LRLT between January 2005 and January 2012. All donors were vaccinated with the HBV vaccine. All patients were given oral antivirals for HBV before transplantation. Patients with HBV DNA levels ≤ 2000 IU/mL were not given HBIG, and patients with HBV DNA levels > 2000 IU/mL were given HBIG. Recurrence was defined as HBV DNA positivity 6 months after transplantation. Seventy‐five of the 89 patients who underwent LRLT for HBV‐related liver disease were not given HBIG. Nineteen patients received a combination of lamivudine and adefovir, 42 received entecavir, 12 received tenofovir, and 2 received a combination of entecavir and tenofovir. At the last follow‐up (median = 21 months, range = 1‐83 months), all patients were HBV DNA–negative. Sixty‐six patients cleared hepatitis B surface antigen (HBsAg), and 19 patients formed antibody to hepatitis B surface antigen (anti‐HBs). The cumulative probabilities of clearing HBsAg were 90% and 92% at 1 and 2 years after transplantation, respectively. Nine patients were HBsAg‐positive with undetectable DNA at the last follow‐up. The recurrence rate in our series was 8% (6/75). Five of these 6 patients had stopped taking oral antivirals, and 1 had entecavir resistance. All recurrences were salvaged with changes in the oral antivirals. The actuarial probability of survival in this cohort was 73.7% at 83 months. There was no mortality due to HBV recurrence. In conclusion, HBV prophylaxis with oral antivirals and without HBIG is safe and effective in LRLT. A majority of the patients will clear HBsAg, and some will develop anti‐HBs antibodies. Liver Transpl 19:1030–1035, 2013. © 2013 AASLD.